Hazard assessment and early warnings of flood disasters in the Yangtze-Huaihe river basin - Jiali Shao; Muzhen Shi; Lianni Xie; Yudi Guo; Shuang Wu (Geomatics, Natural Hazards & Risk)
Conducting flood hazard assessment and establishing effective early warning models before the occurrence of flood can significantly mitigate the impacts. In this study, we take the three-day accumulated precipitation before a flood disaster, predicted daily precipitation and current soil moisture as the disaster-causing factors and combine disaster–pregnant environmental factors such as river network density, terrain and land use type to develop a hazard assessment model for flood disasters in the Yangtze-Huaihe River Basin. Furthermore, we verify the effectiveness and accuracy of the established hazard assessment model. The results show that the warnings provided by the model are basically consistent with the actual disaster reports. The accuracy rate of model for early warnings is 95.64%, the missing rate is only 4.36%, and the area under the receiver operating characteristic curve reaches 0.736, indicating better prediction performance of the model. For different grades of flood disasters, the early warning rate for extreme flood disasters reaches 76.2%. In terms of temporal consistency, the hazard index showed a significant upward trend within 1–3 days before flood, and the index of some disaster areas exceeded 0.7, reaching a high hazard level. Thus, the hazard index has a certain role in early warnings of flood disasters.